2021
DOI: 10.1186/s12301-021-00143-z
|View full text |Cite
|
Sign up to set email alerts
|

Renal leiomyoma: a case report and literature review

Abstract: Background Renal leiomyomas are exceptionally rare, benign, mesenchymal tumours originating from smooth muscle in the kidney. Historically, because of their small size, most renal leiomyoma cases were discovered incidentally based on autopsy findings. However, since the advent and improved access to imaging modalities such as ultrasound and computed tomography (CT), renal leiomyomas are being discovered more frequently. Although usually incidental discoveries, clinical presenting signs and symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Infections contracted during the rst trimester present the gravest outcomes, with a mortality rate of 100%, whereas third-trimester infections show a reduced mortality rate of 57.1%. Nevertheless, the prognosis for pregnant women remains positive, in line with other research ndings [3,10,12,14] .…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Infections contracted during the rst trimester present the gravest outcomes, with a mortality rate of 100%, whereas third-trimester infections show a reduced mortality rate of 57.1%. Nevertheless, the prognosis for pregnant women remains positive, in line with other research ndings [3,10,12,14] .…”
Section: Discussionsupporting
confidence: 84%
“…In healthy individuals, LM infection is usually limited to mild gastrointestinal symptoms. Pregnant patients infected with LM exhibit symptoms ranging from mild respiratory symptoms to mild gastrointestinal symptoms, resembling in uenza or even being asymptomatic [14] . In this study, The predominant symptoms observed in pregnant women were fever, with a body temperature between 38 ℃ and 40 ℃, followed by abdominal pain, reduced fetal movement, and fetal tachycardia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations